DOI: 10.24124/1997/bpgub27
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the major sinks and sources of phosphorus in Tabor Lake: implications for management and remediation

Abstract: A study of Tabor Lake and its watershed during the open water season of 1995 was conducted in order to quantify the major sinks and sources of phosphorus, and the timing of phosphorus transfer between these sources and sinks. The results of this thesis are useful to help determine appropriate management strategies aimed at reducing phosphorus availability in Tabor Lake's water column and understanding some of the processes that control phosphorus availability in the lake.An exploratory modeling exercise was un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Jacoby et al (1982) showed that macrophyte decomposition in Long Lake (Washington) contributes 200-400 kg P to the water column during winter months, with this equating to 25-50% of the total external load. Simmons (1997) reported that macrophyte decomposition in Tabor Lake contributed 1,958 kg P to the water column (44% of total load) during the spring through early autumn 1995, with up to 52% of the P load being contributed by bottom sediments. Although macrophyte decomposition/translocation in Nulki and Tachick lakes might also contribute significant P loads, macrophyte-associated loads to Charlie Lake would be minimal because the lake's macrophyte community is very sparse (T. French, unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…Jacoby et al (1982) showed that macrophyte decomposition in Long Lake (Washington) contributes 200-400 kg P to the water column during winter months, with this equating to 25-50% of the total external load. Simmons (1997) reported that macrophyte decomposition in Tabor Lake contributed 1,958 kg P to the water column (44% of total load) during the spring through early autumn 1995, with up to 52% of the P load being contributed by bottom sediments. Although macrophyte decomposition/translocation in Nulki and Tachick lakes might also contribute significant P loads, macrophyte-associated loads to Charlie Lake would be minimal because the lake's macrophyte community is very sparse (T. French, unpubl.…”
Section: Discussionmentioning
confidence: 99%